(untitled) (Atti del Sodalizio Glottologico Milanese, 2025)
The paper addresses the relation between the gəzêrāh šāwāh, which is an analogy-based argumentative strategy typical of rabbinic exegesis, and so-called combined citations, that is, combinations of disparate Old Testament passages into a single quotation. Although gəzêrōṯ šāwōṯ and combined citations represent neatly different devices, a clear dividing line is not always traced in the literature, as both exhibits a few similarities. By examining some cases of combined citations in Paul’s letters, I discuss the similarities and the differences between gəzêrōṯ šāwōṯ and combined citations. The investigation reveals that Paul skillfully adapted the rabbinic technique into a citation strategy.